Analisis Dan Perancangan Sistem Pendukung Keputusan Penerimaan Beasiswa Menggunakan Metode Simple Additive Weighting Pada SMAN 5 Kota Jambi - Arfiandi, Idris; Sarjono, Sarjono (Jurnal Manajemen Sistem Informasi, 2020)
Education has a very important role in people's lives, but the huge cost of education is an obstacle formany people to be able to continue their education. The government provides educational assistancethrough the assistance of one student's scholarship. Therefore it is necessary to build a Decision SupportSystem (SPK) to solve the problem. In determining the acceptance of scholarships, there are many criteriathat must be owned by individuals as a condition in getting a scholarship. Each school must have criteriato determine who will be selected to receive a scholarship. Distribution of scholarships is done by severalinstitutions to help someone who is less capable or achievers during their studies. To help determine whois eligible to receive a scholarship, a decision support system is needed. In this study, a case will beraised, namely finding the best alternative based on predetermined criteria using the SAW (SimpleAdditive Weighting) method. The study was conducted by finding the weight value for each attribute,then the ranking process was carried out which would determine the optimal alternative, namely the beststudents.